Domino Sonogashira coupling/metal carbene-involved annulation enabled by Pd/Cu relay catalysis: rapid assembly of indazole-containing biheteroaryls. Issue 9 (28th March 2023) - Ding, Ruiming; Cui, Haili; Zhu, Yongyan; Zhou, Yao; Tao, Huaming; Mai, Shaoyu
Abstract : An efficient and novel method has been developed for the synthesis of indazole-containing biheteroaryls via a domino Sonogashira coupling/azaenyne cycloisomerization/Barton–Kellogg reaction. Abstract : An efficient and novel method has been developed for the synthesis of indazole-containing biheteroaryls via a domino Sonogashira coupling/azaenyne cycloisomerization/Barton–Kellogg reaction. The new scalable protocol leads to a broad array of substituted indazole-containing biheteroaryls under mild reaction conditions. Compared to classical domino Sonogashira coupling/cyclization, this powerful strategy enables simultaneous generation of two heterocycles, especially the two C-atoms of a terminal alkyne are, respectively, incorporated into two different rings. Preliminary mechanistic studies demonstrate that the CuI catalyst has multiple roles, guaranteeing the connection of each reaction smoothly. Remarkably, this work represents an unprecedented example of domino Sonogashira coupling/metal carbene-involved annulation.